On the Production, Mating and Behavior of Males in Synoeca surinama (Vespidae: Polistinae: Epiponini) - Dos Santos, C. A. [UNESP]; Da Silva, M. [UNESP]; Noll, F. B. [UNESP] (Univ Estadual Feira Santana, 2020)
In colonies of Neotropical swarm-founding wasps (Epiponini), males are thought to be produced only in periods when there are many queens present. Little information is available regarding male behavior in and out of the nest, and male mating strategies are poorly understood. Here, a behavioral study of males of Synoeca surinama is provided and copulation behavior inside a nest is described for the first time. A description of an aggregation of non-natal males at a nest is also provided. The behavior of males was observed in three colonies subjected to removal of queens for another study. Nest envelope was partially removed, and the observations were made directly (seen by the naked eye) and indirectly (through camcorder recordings), daily. Production of males occurred in large colonies with number of workers being more relevant than the number of the queens. Males of the aggregation were marked and filmed. The aggregation of non-natal males was observed for seven consecutive days next to the largest colony; some of the males attended the aggregation on consecutive days. The males were observed accessing the comb by the opening in the envelope and courting new queens. One successful copulation on the comb of the nest was observed. In the colony where the male aggregation was observed, 47.6% of the new queens were inseminated while in the other two colonies, no new queens were inseminated. These observations suggest males are attracted to, aggregate and seek mating opportunities at non-natal colonies that are producing young adult queens.
Keywords: Copulation; male aggregation; reproductive behavior; swarm founding wasps